Corrosion Protection of Heat Treated Carbon Steel Surfaces By Passivity in the Industrial Atmospheres (Engineering and Technology Journal, 2010)
The object of this research is to study the passivity of surfaces of heat treated medium carbon steel (CK45) by annealing, spheroidise annealing, normalising, and water hardening. This research also studies corrosion resistance of corrosion protected samples by passivity in the industrial atmospheres for two periods (720 hr. and 1440 hr.).The results, which have been obtained, show that the corrosion rates in the unprotected samples are high compared with the corrosion protected samples by passivity.